2014
DOI: 10.1002/pd.4537
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the myocardial performance index in deteriorating grades of intrauterine growth restriction and its link to adverse outcomes

Abstract: Fetal myocardial performance deteriorates with severity of growth restriction. There is an association between severity of the MPI elevation and rates of adverse perinatal outcome. The Mod-MPI and E/A ratio have the potential to be integrated into routine surveillance techniques of the growth-restricted fetus. © 2014 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 28 publications
4
42
1
4
Order By: Relevance
“…In contrast, clinical utility of MPI has been suggested by other studies in Table S1, including recent work of Bhorat et al ,. who found MPI to be 35% higher in FGR cases than in controls as well as higher MPI with worsening FGR, and Nassr et al ,.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, clinical utility of MPI has been suggested by other studies in Table S1, including recent work of Bhorat et al ,. who found MPI to be 35% higher in FGR cases than in controls as well as higher MPI with worsening FGR, and Nassr et al ,.…”
Section: Discussionmentioning
confidence: 91%
“…In the current study, we found no significant difference between the Mod‐MPI measurements of normal‐growth fetuses vs those of fetuses with FGR. However, many previous studies suggested that this index was useful in FGR . To shed light on the potential utility of the Mod‐MPI, we performed a statistical analysis of data on fetuses with FGR and AED flow on US Doppler evaluations and data obtained from normal‐growth fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…MPI levels are expected to change in the presence of pathological conditions that influence fetal cardiac functions. These include fetal growth restriction (FGR), twin‐twin transfusion syndrome, maternal diabetes mellitus, preeclampsia, fetal hydrops, and fetal anemia . When fetal cardiac functions influence the MPI, it may be important to decide the time of the birth.…”
Section: Introductionmentioning
confidence: 99%
“…Because of such discrepancies, although many studies have assessed cardiac function in various complicated conditions, their value in clinical practice is limited. Recent studies suggested cut‐off Mod‐MPI values for predicting adverse outcomes in gestational diabetes and IUGR . However, these studies did not describe cursor placement (i.e.…”
Section: Discussionmentioning
confidence: 99%